Asymmetry in contraceptive information at two sites in Burkina FasoAJOG Global Reports at a Glance - Leigh Senderowicz, ScD; Brooke W. Bullington, BA; Nathalie Sawadogo, PhD; Katherine Tumlinson, PhD (Elsevier, 2024)
Background: Family planning programs are foundationally important to public health, but like any medical intervention, contraception has drawbacks in addition to its benefits. Knowledge of these drawbacks in addition to benefits is essential for informed choice. Despite a general consensus among family planning researchers and providers that contraceptive counseling should be unbiased, little quantitative research has assessed the extent of bias in contraceptive counseling, and in people's contraceptive knowledge more broadly. Objective: To understand the extent to which women report being told more about the advantages of contraception than the disadvantages-a concept we call "asymmetry" in contraceptive counseling, at two research sites in Burkina Faso. Methods: We use data from a cross-sectional population-based survey of 3,929 women residing in the catchment areas of the Ouagadougou (urban) and the Nouna (rural) Health and Demographic Surveillance Systems in Burkina Faso. We use descriptive statistics to explore asymmetry in knowledge of the benefits/advantages and risks/disadvantages of contraceptive use overall, as well as method-specific asymmetry among current method users regarding their counseling experience. Findings: Results show substantial asymmetry in knowledge of advantages/benefits of contraception compared to disadvantages/risks. 86% of respondents said they could name any advantage of family planning, while half of that proportion (43%) could name any disadvantage. We find a similarly stark asymmetry in method-specific results among contraceptive users, especially for hormonal/biomedical methods. We also find substantial variation between research sites, with urban respondents much less likely to self-report complete family planning knowledge than their rural counterparts. Conclusion: Our results suggest that family planning messaging in Burkina Faso may place an emphasis on the advantages without a commensurate focus on disadvantages. Family planning programs worldwide must ensure that people can make informed choices based on balanced, accurate information about both the benefits and the disadvantages of contraception.